Distribution of Dendritic Cells and Langerhans Cells in Peri-implant Mucosa - Gooty, Jagadish Reddy (Contemp Clin Dent, 2018)
BACKGROUND: Peri-implant diseases leading to the failure of dental implants is concern in the field of dentistry. Difference in immune response around peri-implant tissues with healthy tissue might be responsible for the hidden cause of peri-implant diseases. Hence, in the current study, the dispersion of the dendritic cell (DC) subpopulations and Langerhans cells (LCs) was evaluated in healthy peri-implant mucosa (HPIM) and healthy mucosa (HM) to know the imbalance in immune homeostasis. SUBJECTS AND METHODS: A total of 15 nonsmoker participants were selected for the study. First sample of the HM was obtained before the implant placement (Group I) and second sample of peri-implant mucosa was obtained at the time of placement of the gingival former (Group II). Immunochemistry was used to quantify DCs and LCs in the samples. STATISTICAL ANALYSIS USED: To analyze the distribution of cells in the epithelium and lamina propria, Wilcoxon matched pairs test was used. RESULTS: Mean numbers of CD1a (LCs) in the epithelium and lamina propria of Group I and Group II were 25.2 ± 6.41 and 27.47 ± 10.26 and 19.27 ± 7.27 and 12.46 ± 3.04, respectively. Mean numbers of factor XIIIa (DCs) in the epithelium and lamina propria in Group I and Group II were 30.37 ± 5.42 and 86.93 ± 13.99 and 50.47 ± 7.27 and 124.33 ± 10.27, respectively. Statistically significant differences in the number of cells in the epithelium and lamina propria of Group I and Group II were noted (P = 0.001 and P = 0.001). CONCLUSIONS: CD1a-positive LCs were more in the epithelium rather than lamina propria in Group II. Higher numbers of factor XIIIa-positive DCs were observed in the lamina propria than epithelium in Group I and II.